Sub-optimal satisfaction of people living with HIV and AIDS regarding their care in Burkina Faso, West Africa - Smaïla Ouédraogo; Ter T.E. Dah; Ismaël Diallo; Maurice Sarigda; Désiré L. Dahourou; Issa Romba; Fatogoma B. Sanon; Pengdwendé A.L. Kaboré; Bapougouni P.C. Yonli; Léon G.B. Savadogo (AOSIS, 2023)
People living with HIV (PLHIV) satisfaction regarding to care could play an important role in the elimination of HIV epidemic by 2030. We assessed Burkina Faso PLHIV satisfaction regarding to their care, and identified its associated factors. A representative nationwide cross‑sectional study was performed in 2021‑2022 in 30 HIV/AIDS care sites. PLHIV aged at least 18 years, receiving ART for six months or plus were included. Individual and structural data were collected using a questionnaire administered by trained investigators. Satisfaction with HIV/AIDS care was explored using six components (reception, waiting time to medical visit, care environment, sharing updated information on HIV AIDS, answering to PLHIV questions, and providing tailored care and advice to PLHIV needs). Factors associated with satisfaction were identified using logistic regressions. 448 PLHIV were considered in this analysis. Median age was 46 years. Overall satisfaction regarding to care was 40,8% (95% confidence interval 95% CI 36.2‑45.6). Specifically, it was 90.6, 54.9, 85.3, 75.7, 90.8, and 93.3% regarding to reception, waiting time, care environment, sharing updated information, answering to PLHIV questions, and providing tailored care and advice to PLHIV needs, respectively. Attending to medical visits in community‑based organization (CBO) and private clinics (adjusted odds ratio aOR 1.82, 95% CI 1.14‑2.93, P0.001), as well as in tertiary hospitals (aOR 2.37, 95% CI 1.45‑3.87, P=0.001) were positively associated with PLHIV satisfaction. Burkina Faso PLHIV are generally unsatisfied with care. HIV national authorities should promote HIV care in CBO clinics model in the delivery of HIV services in others public sites.